Toxicity of combined sewer overflows on river phytoplankton: the role of heavy metals - Seidl, M.; Huang, V.; Mouchel, J.M. (Environmental Pollution, 1998)
The toxic effect of a combined sewer overflow (CSO) on the phytoplankton community of the river Seine has been studied by means of short-term primary production measurements. As the discharged solids usually do not remain in the water column, only filtered or centrifugated fractions were tested. The collected phytoplankton were grown in the laboratory for 2 days, after addition of N, P and EDTA. Stock cultures in exponential growth were directly tested with heavy metals, but resuspended algal cells were used for effluent testing. The results show an increase of EC50 value for the single metal species in the order Cu<<Zn less than or equal to Pb. Free metal contents were calculated with the chemical speciation model Mineql +. The EC50 dilution of the tested CSOs effluent was 50%. This value increased by 30% after addition of 5 10(-6) M EDTA, indicating that the effluent toxicity is only partially due to its metallic compounds. (C) 1998 Elsevier Science Ltd. All rights reserved.